INTERPRETASI KAJIAN PUISI "SETITIK NUR" KARYA HAMID JABBAR - Naufal, Mochammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
In addition to being a means of communication between humans, sound can also be a source of beauty and decoration in evoking the atmosphere or feelings of one's soul. Sound is always associated with songs, rhythms, melodies, and so on. Its role is not only as a decoration and sweetener, but the sound issued must be able to sharpen the meaning, the right sound can help in conveying oral messages because it can create its own atmosphere. Sounds in poetry involve elements of rhyme, assonance, alliteration, efony and kakafoni, onomatopoeia and symbols of taste.